2021
DOI: 10.3390/jof7090727
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Combinations in Dermatophytes

Abstract: Dermatophytes are the most common cause of fungal infections worldwide, affecting millions of people annually. The emergence of resistance among dermatophytes along with the availability of antifungal susceptibility procedures suitable for testing antifungal agents against this group of fungi make the combinatorial approach particularly interesting to be investigated. Therefore, we reviewed the scientific literature concerning the antifungal combinations against dermatophytes. A literature search on the subjec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 91 publications
1
27
0
Order By: Relevance
“…It is known that such compounds are lipophilic and have a small molecular size which enable their passive diffusion through fungi membranes [16]. Volatile compounds exert their fungicidal activity through different mechanisms of action that include, among others, the perturbation of the lipid membrane organization [60] followed by the increased permeability of the fungal cell wall/membrane, the extravasation of cell constituents, the inhibition of ergosterol synthesis, and cell lysis [15,23]. Moreover, it was reported that several main constituents of the Apiaceae EOs included in our study acted on the virulence factors and resistance mechanisms of T. rubrum.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is known that such compounds are lipophilic and have a small molecular size which enable their passive diffusion through fungi membranes [16]. Volatile compounds exert their fungicidal activity through different mechanisms of action that include, among others, the perturbation of the lipid membrane organization [60] followed by the increased permeability of the fungal cell wall/membrane, the extravasation of cell constituents, the inhibition of ergosterol synthesis, and cell lysis [15,23]. Moreover, it was reported that several main constituents of the Apiaceae EOs included in our study acted on the virulence factors and resistance mechanisms of T. rubrum.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the lipophilic nature of EOs components, their high volatility and chemical instability, the encapsulation in nanoformulated delivery systems could be an approach to overcome such limitations and boost the antidermatophytic activity of EOs [15,22,82]. The additional data regarding their skin and nail permeation, elucidation of their mechanism of activity, and whether in vitro results translate into similar outcomes in in vivo models, are in high demand.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Combination therapy associating antifungal drugs is already used to improve the monotherapy results in clinical settings of refractory dermatophytosis [28,29]. In addition, combinatorial strategies associating conventional drugs (e.g., terbinafine) and plant phenolics have already been proposed as a complementary therapy against dermatophytes [21,30].…”
Section: Discussionmentioning
confidence: 99%